PENILAIAN KELAYAKAN PENGEMBANGAN EKOWISATA PEMANDIAN ALAM GUNUNG PANDAN DI KECAMATAN TENGGULUN KABUPATEN ACEH TAMIANG - Iswahyudi iswahyudi; Rosmaiti Rosmaiti (Forestry Study Program University Of Mataram, 2022)
Ecotourism of the Gunung Pandan Natural Baths, which is located in Selamat Village, Tenggulun District, is one of the priority scales for tourism development in Aceh Tamiang Regency. The development of ecotourism is believed to be able to maintain the conservation of natural resources and improve the welfare of the surrounding community. This study aims to assess the feasibility of developing ecotourism at the Gunung Pandan Natural Baths. The assessment of potential tourism objects uses the Guidelines for Operation Areas for Natural Tourism Attractions (ADO-ODTWA) issued by the Director General of PHKA of the Ministry of Forestry in 2003. The results of the ADO-ODTWA analysis show that the Gunung Pandan Natural Baths as a conservation area are worthy of being developed as an ecotourism destination, with a recapitulation potential value index of 83.39%. Some criteria that need attention and improvement are accessibility and security. Improving the two components is a priority to develop the Gunung Pandan Natural Bath Ecotourism area into a leading ecotourism destination.